Cross-cultural Adaption and Validation of the Zurich Chronic Middle Ear Inventory Translated Into Italian (ZCMEI-21-It)—a Prospective Multicenter Study. Issue 3 (March 2019) - Ralli, Massimo; Quaranta, Nicola; Canale, Andrea; Röösli, Christof; Milella, Claudia; De Robertis, Valentina; De Soccio, Giulia; Greco, Antonio; Ralli, Giovanni; Albera, Roberto; de Vincentiis, Marco; Huber, Alexander M.; et al.
Abstract : Objective: There are no instruments available to comprehensively assess health-related quality of life (HRQoL) in chronic otitis media (COM) in Italian-speaking countries. The Zurich chronic middle ear inventory (ZCMEI-21) is a well-established instrument for the assessment of HRQoL in COM. The objective of this study was to translate and cross-culturally adapt the ZCMEI-21 into Italian and validate this questionnaire for measuring HRQoL in patients with COM. Study Design: Prospective multicenter study. Setting: Three University hospitals (northern Italy, central Italy, southern Italy). Patients: Adult patients suffering from COM (n = 128). Intervention: Following international guidelines, the ZCMEI-21 was translated into Italian (ZCMEI-21-It). Validation was performed by psychometric test statistics. Moreover, ZCMEI-21-It total and subscale scores were compared and correlated with 1) the scores of the original validation study, 2) to a question that directly addresses HRQoL, and 3) to the scores of the EQ-5D-5L, a generic questionnaire assessing HRQoL. Results: From three study centers, a total of 128 patients with COM were included. Cronbach's α was 0.86 indicating a high reliability. Between the ZCMEI-21-It total score and the question that directly addresses HRQoL, we found a strong correlation (r = 0.62, p < 0.0001). Between the ZCMEI-21-It total score and the EQ-5D-5L scores, we expectedly found moderate correlations (descriptive system score: r = 0.39, p < 0.0001; visual analog scale: r = 0.30, p = 0.008). Conclusion: We translated the ZCMEI-21 questionnaire into Italian and validated the ZCMEI-21-It in a prospective multicenter study. The ZCMEI-21-It is the first instrument that comprehensively assesses relevant dimensions of HRQoL in Italian-speaking patients affected by COM. Abstract : Supplemental Digital Content is available in the text